#### To determine

**To find:** We have to solve the equation e3x+1=k for x.

#### Answer

The solution of the equation is x=lnk-13.

#### Explanation

**Calculation:**

First, we are taking natural logarithmic on both sides of the equation e3x+1=k.

Thus, we have

lne3x+1=lnk

Since we know that

lnex=x (1)

Thus, using equation (1), we have

3x+1=lnk,

Or 3x=lnk-1

x=lnk-13.

**Conclusion:**

The solution of the equation is x=lnk-13.

#### To determine

**
To find:** We have to solve the equation **-** log2(mx)=**c,** for x.

#### Answer

The solution of the equation is x=1m2c.

#### Explanation

Formula used: log2x=y if and only if x=2y.

Calculation:

log2(mx)= c,

Using the above formula, we have

mx=2c or x=1m2c

**Conclusion:**

The solution of the equation is x=1m2c.